N-Doped rGO-like carbon prepared from coconut shell: structure and specific capacitance - Khambali, Imam; Priyanto, Budhi; Asih, Retno; Anjelh Baqiya, Malik; Mahyiddin Ramli, Muhammad; Huda Osman, Nurul; Tunmee, Sarayut; Nakajima, Hideki; Triwikantoro, .; Zainuri, Mochamad; Darminto, . (Tech Science Press, 2022)
An rGO−like carbon compound has been synthesized from biomass, i.e., old coconut shell, by a carbonization process followed by heating at 400°C for 5 h. The nitrogen doping was achieved by adding the urea (CH4N2O) and stirring at 70°C for 14 h. The morphology and structure of the rGO-like carbon were investigated by electron microscopies and Raman spectroscopy. The presence of C-N functional groups was analyzed by Fourier transform infrared and synchrotron X-ray photoemission spectroscopy, while the particle and the specific capacitance were measured by particle sizer and cyclic voltammetry. The highest specific capacitance of 72.78 F/g is achieved by the sample with 20 urea, having the smallest particles size and the largest surface area. The corresponding sample has shown to be constituted by the appropriate amount of C–N pyrrolic and pyridinic defects.